English Language Proficiency and Academic Performance of Grade VI Pupils in Selected Elementary Schools in Subic, Zambales - Alib, Maribel Barade (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigates the relationship between English language proficiency and academic performance among Grade VI pupils in selected elementary schools in Subic, Zambales. Employing a descriptive research design, data were gathered from 400 pupils through surveys and documentary analysis. The study assessed the pupils' proficiency in four key language skills listening, speaking, reading, and writing and examined their academic performance in English, Mathematics, and Science. Results indicated that pupils exhibited a good level of proficiency in listening and reading (receptive skills) and a very good level in speaking and writing (productive skills). In terms of academic performance, pupils achieved satisfactory levels in English, Mathematics, and Science. Significant differences were observed in the proficiency levels of the four macro skills, with listening and reading skills correlating strongly with academic performance in Mathematics. Furthermore, a significant relationship was found between English proficiency and academic achievement, suggesting that enhanced language skills positively impact performance in other subjects, particularly in Mathematics and Science. The study emphasizes the importance of improving receptive language skills to foster academic success in these subjects. Based on these findings, the study recommends that educators prioritize the development of both receptive and productive language skills. Future research is encouraged to further explore the complementary relationship of these skills with academic performance and to validate the results of this study through follow-up investigations.